STATE CAPACITY IN LAND MANAGEMENT AND SPATIAL PLANNING: A COMPARATIVE STUDY OF INDONESIA-SINGAPORE - Syahrial, Ony; Aminullah (International Journal of Multidisciplinary Reseach, 2025)
Land and spatial governance constitute strategic policy domains for ensuring sustainable and equitable development. This study aims to analyze differences in state capacity between Indonesia and Singapore in managing land and spatial planning and to examine their implications for policy effectiveness and land-related conflicts. The research adopts a qualitative approach with a descriptive–comparative design, employing a literature review of academic publications, policy documents, and reports from national and international institutions. The analysis focuses on four key dimensions of state capacity: regulatory framework, institutional arrangements, policy implementation, and oversight mechanisms.The findings indicate that although Indonesia possesses a relatively comprehensive regulatory framework through Law No. 26 of 2007 on Spatial Planning, its state capacity in implementation remains constrained by fragmented authority under decentralization, weak cross-sectoral coordination, and inconsistent law enforcement. In contrast, Singapore demonstrates a high level of state capacity through a centralized spatial planning system managed by the Urban Redevelopment Authority (URA), strong state control over land ownership, and consistent long-term planning instruments, notably the Concept Plan and Master Plan. These conditions contribute to a high degree of legal certainty and a significant reduction in land-use conflicts. This study concludes that state capacity is a critical determinant of effective land and spatial governance and offers policy-relevant insights for strengthening spatial governance in Indonesia.